ILLEGAL FISHING DI PERAIRAN NATUNA: PERMASALAHAN DAN UPAYA PENANGANANNYA - Narulita, Indhy; Putri, Silva; Ramdhana, Surya Dinar; Hotimah, Oot (Jurnal Samudra Geografi, 2025)
Natuna waters, as one of Indonesia's resource-rich marine areas, are the main targets of illegal fishing. Illegal fishing, which includes unlicensed fishing or violations of applicable fishing rules, has had a serious impact on the economy, sustainability of fishery resources, and social stability in the region. This paper discusses the influence of illegal fishing as a form of economic crime in Natuna waters, focusing on the economic impact caused by this illegal practice. We also reviewed the efforts made by the Indonesian government and related parties to address this problem. This study highlights the importance of regional and international cooperation in dealing with illegal fishing, given the global impact it has on fish stocks and marine ecosystems. By analyzing the root problems, economic consequences, and possible solutions, the writing aims to better understand the role of illegal fishing in threatening the economy and the highly valuable environment in Natuna waters.